RF characterization of power dividers/combiners and directional couplers - Rigodon, Lorimer P. (2004)
This research project characterized the performance of microwave directional couplers and power dividers fabricated into various types of printed circuit boards. FR4 and RO boards were used in the fabrication and investigated separately based on how it affects the device's performance. Fabrication was done using the milling machine for precise etching but chemical etching was also considered to provide a clear comparison of how the other procedure outweights the other. Analysis of common discontinuities that can be found in planar microwave transmission structures were done as well as the formulation of its corresponding compensations that helped in optimizing the microwave devices' performance. The repeatability of the two methods was also investigated. The directional couplers and power dividers were simulated using Microwave Office - 225 to provide simulated data in which actual data were compared. Results of the project includes the evaluation as well as the comparison of the various types of circuit boards based on how the couplers and power dividers perform on each of them, comparison of different fabrication methods, analysis of the de-embedding technique and the effects of compensation on the devices' performance, test on the repeatability of the procedures, and lastly, the comparison of the actual data gathered to simulated data. Careful evaluation of the results showed that factors affecting the performance of the directional couplers and power dividers have different degree of effects on the variation of the measured test parameters to the simulation results.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Directional couplers; Radio frequency; Radio circuits; Power dividers; Power combiners